Blowback Operations as Rebel Strategy: How Sectarian Violence Spread from Syria into Lebanon, 2013–14 - Hägerdal, Nils (Terrorism and political violence, 2023)
Why and how do conflict and violence spread across international borders? This article introduces a new theoretical framework for blowback operations, where a civil war combatant launches terrorist attacks in the home country of a foreign actor to compel this actor to end a military intervention. Using this framework, we explain how military intervention by Hezbollah in Syria sparked a bombing campaign by Sunni jihadi groups inside Lebanon. Novel quantitative and qualitative evidence reveals how perpetrators deployed violence strategically to maximize their coercive leverage. Rather than indiscriminately attacking Lebanese Shia civilians—as their hardline sectarian discourse would suggest—Jihadi groups, including local Al Qaeda and ISIS affiliates, primarily targeted Hezbollah political strongholds to force it to withdraw from Syria. Hezbollah, seeking domestic stability due to its strong position in the Lebanese political system, generally responded with restraint and thereby avoided escalating the episode into civil war. The growing reach and prominence of armed non-state actors, especially across the Middle East, increasingly make their cross-border operations an important feature of sub-state conflict.